Adaptação cultural e validação de conteúdo do sistema de triagem de Manchester versão inglesa para o português do Brasil. - Flavia de Oliveira (2017)
The Manchester Triage System (MTS) is a protocol that has been used in healthcare facilities in Brazil to make the risk classification and guarantee the immediate care of users with high life risk. To be used in Brazil, the Risk Classification Group made the translation into Brazilian Portuguese. However, translation is the first step in the process of cultural adaptation. In this sense, it is necessary to improve the MTS, since studies have not yet been performed for its adaptation and validation. Objective: To carry out the cultural adaptation and validation of the content of the 3rd English version of origin of the MTS for Brazilian Portuguese. Method: Methodological study carried out in five stages: translation, synthesis, retro-translation and evaluation by a committee of judges. The process was mediated and evaluated by the researcher. After each round, content validation was performed from a minimum inter-observer agreement of 80%. Results: From the translated versions T1 and T2 a synthesis version was generated for the Portuguese language of Brazil. Rounds were necessary for language adequacy to obtain the final translated version (Ts). In back-translation, although the writing is not exactly the same as the one used in the original version, most of the time the phrase and its context have kept the same meaning as the original version. In the flowcharts and dictionary of discriminators, points of divergence that were solved were found, so it was not necessary to make any modification in the Ts version of the flowcharts and some modifications in the discriminators. The judges committee lasted 90 days, with three rounds for the flowcharts and two rounds for the discriminator dictionary. At the end, a descriptive analysis of the version found in this study was carried out in comparison with the second version used in Brazil, where there were significant differences in the translation of the discriminators in addition to the inclusion of discriminators in the flowcharts with changes in the order of priority in the waiting time for the first medical care. Final considerations: cultural adaptation and validation of instrument content for use in a culture other than the original one was constructed requires careful method to obtain semantic, idiomatic, cultural and conceptual equivalence between languages. This study contributes to the improvement of MTS and collaborates with the nurse, in the decision making, enabling the substitution of terms by those closest to Brazilian reality and culture.